A burrowing ecosystem engineer positively affects its microbial prey under stressful conditions. Issue 13 (13th June 2019) - Bell, Laura; Cuddington, Kim
Abstract: Species that facilitate others under stressful conditions are often ecosystem engineers: organisms that modify or create physical habitat. However,  the net effect of an engineering species on another depends on both the magnitude of the direct interactions (e.g., competition or predation) and the specific environmental context. We used a laboratory system to isolate the trophic and engineering impacts of a predator, the nematode Caenorhabditis remanei, on its prey, Escherichia coli under different levels of environmental stress. We predicted that under stressful surface conditions the nematodes would positively impact their prey by creating burrows which protected the bacteria. Colony plate counts of E. coli indicated that there was a stress‐induced change in the net impact of nematodes on bacteria from neutral to positive. Predator engineering in the form of burrowing allowed larger bacteria populations to survive. We conclude that even in a simple two‐species system a predator can positively impact prey via ecosystem engineering. Abstract : Ecosystem engineering Caenorhabditis elegans can positively affect their prey, Escherichia coli, when surface conditions are stressful. a) Before stress, burrowing present, b) after stress, burrowing present, c) before stress, no burrowing, d) after stress, no burrowing.